2018
DOI: 10.1097/iae.0000000000001508
|View full text |Cite
|
Sign up to set email alerts
|

ASSOCIATION STUDY BETWEEN POLYMORPHISMS OF THE p53 AND LYMPHOTOXIN ALPHA (LTA) GENES AND THE RISK OF PROLIFERATIVE VITREORETINOPATHY/RETINAL DETACHMENT IN A MEXICAN POPULATION

Abstract: The C allele for rs1042522 in p53 was genetically associated with a higher risk for RD but not for PVR in this cohort. This is the first association study attempting replication of PVR-associated risk alleles in a nonwhite population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Some of them have identified specific SNPs located in genes involved in the PVR pathways, which may be involved in the disease pathogenesis and represent potential predictive factors for PVR development [ 9 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Some genetic association studies performed in the last two decades have also highlighted the potential of various gene polymorphisms of inflammatory mediators and growth factors as new biomarkers in PVR pathogenesis as well as a potential tool in its diagnosis and treatment [ 9 , 29 , 30 , 32 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of them have identified specific SNPs located in genes involved in the PVR pathways, which may be involved in the disease pathogenesis and represent potential predictive factors for PVR development [ 9 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Some genetic association studies performed in the last two decades have also highlighted the potential of various gene polymorphisms of inflammatory mediators and growth factors as new biomarkers in PVR pathogenesis as well as a potential tool in its diagnosis and treatment [ 9 , 29 , 30 , 32 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quiroz-Casian and colleagues genotyped 380 Mexican patients (180 patients with IRD and 200 matched controls) for rs1042522 in the p53 gene; this gene had previously been found to influence proliferative vitreoretinopathy development in patients of European ancestry [ 33 ]. The study found the C allele conferred 1.4 increased odds of RD (95% CI 1.01–1.9 OR:1.4) in this population.…”
Section: Genetic Mutations In Idiopathic Retinal Detachmentmentioning
confidence: 99%